PERFORMANCE RANKING OF DIPLOMA INSTITUTIONS BASED ON SOME SELECTED CRITERIA BY APPLYING SCORING MODEL- A SAMPLE STUDY - Naskar, Sukanta Kumar; Bose, Dipankar; Ghosal, Sujit (Journal of Technical Education and Training, 2010)
The assessment of institutional performance based on various contributing parameters is of paramount importance for an institute and is not an easy task. Present studies aim at assessing the institutional level performance of some selected diploma level institutions of West Bengal by using Scoring Model (SM) - as a multiple criterion decision making technique. Application of this model also shows a comparison of institutions based on their performance with respect to specific contributing parameters.